Treatment of Alzheimer's Disease subjects with expanded non-genetically modified autologous natural killer cells (SNK01): a phase I study - Clemente Humberto Zúñiga; Blanca Isaura Acosta; Rufino Menchaca; Cesar A. Amescua; Sean Hong; Lucia Hui; Minchan Gil; Yong-hee Rhee; Sangwook Yoon; Minji Kim; Paul Y. Chang; Yong Man Kim; et al. (Alzheimer’s Research & Therapy)
Abstract Background The importance of natural killer (NK) cells of the innate immune system in neurodegenerative disease has largely been overlooked despite studies demonstrating their ability to reduce neuroinflammation (thought to be mediated by the elimination of activated T cells, degradation of protein aggregates and secretion of anti-inflammatory cytokines). SNK01 is an autologous non-genetically modified NK cell product showing increased activity in vitro. We hypothesized that SNK01 can be safely infused to reduce neuroinflammation in Alzheimer’s Disease (AD) patients. Methods SNK01 was produced and characterized for its ability to eliminate activated T cells, degrade protein aggregates and secrete anti-inflammatory cytokines. In this phase 1 study, SNK01 was administered intravenously every three weeks for a total of 4 treatments using a 3 + 3 dose escalation design (1, 2 and 4 × 109 cells) in subjects with either mild, moderate, or severe AD (median CDR-SB 10.0). Cognitive assessments and cerebrospinal fluid biomarkers associated with protein aggregation, neurodegeneration and neuroinflammation including amyloid-β42 and 42/40, α-synuclein, total Tau, pTau217 and pTau181, neurofilament light, GFAP and YKL-40 analyses were performed at baseline, at 1 and 12 weeks after the last dose. The primary endpoint was safety; secondary endpoints included changes in cognitive assessments and biomarker levels. Results In preclinical in vitro studies, SNK01 were able to uptake and degrade the protein aggregates of amyloid-β and α-synuclein, produce anti-inflammatory cytokines and eliminate activated T cells. In the phase 1 clinical study, eleven subjects were enrolled (10 evaluable). No drug-related adverse events were observed. Despite 70% of subjects being treated at relatively low doses of SNK01 (1 and 2 × 109 cells), 50–70% of all enrolled subjects had stable/improved CDR-SB, ADAS-Cog and/or MMSE scores and 90% had stable/improved ADCOMS at one-week after the last dose. SNK01 also appeared to have beneficial effects on protein aggregate levels and neuroinflammatory biomarkers in the cerebrospinal fluid, with decreases in pTau181 and GFAP appearing to be dose-dependent. Conclusions SNK01 was well tolerated and appeared to have clinical activity in AD while also having beneficial effects on cerebrospinal fluid protein and neuroinflammatory biomarker levels. A larger trial with a higher dosing/duration has been initiated in the USA in 2023. Trial registration www.clinicaltrials.gov NCT04678453, date of registration: 2020–12-22.